To determine the correct function notation based on the recursively defined formula given, we can break it down.
- The first value of the sequence is defined as \( a_1 = -3 \).
- The recursive formula states that \( a_n = a_{n-1} + 4 \).
Let's look at the options provided:
- Option 1:
\( f(1) = -3 \)
\( f(n) = f(a_{n-1}) + 4 \) - Option 2:
\( f(1) = -3 \)
\( f(n) = f(n-1) + 4 \) - Option 3:
\( a(1) = -3 \)
\( f(n) = f(n-1) + 4 \) - Option 4:
\( f(1) = -3 \)
\( f(n) = a_{n-1} + 4 \)
Now evaluating these:
- Option 1 introduces \( f(a_{n-1}) \) which does not match \( a_n \)’s recursive relationship.
- Option 2 correctly defines the recursive relationship using \( f(n) = f(n-1) + 4 \). This mirrors the behavior of the sequence where each term is the previous term plus 4.
- Option 3 incorrectly uses \( a(1) \) instead of \( f(1) \) and states a relationship for \( f\) which is not equivalent to \( a_n\).
- Option 4 states \( f(n) = a_{n-1} + 4 \), but does not use the recursive nature of \( f\).
Given these evaluations, Option 2 is the correct function notation:
f(1) = -3; f(n) = f(n-1) + 4.